40 Resilience of the ocular microbiome in beef calves. (30th November 2020) - Bartenslager, Alison; Aluthge, Nirosh; Loy, John; Spangler, Matthew; Fernando, Samodha
Abstract: Infectious Bovine Keratoconjuctivitis (IBK), or more commonly known as pinkeye, impacts the beef cattle industry with expenses reaching close to 150 million dollars annually. Thus far, successful prevention of infectious outbreaks of IBK have been limited. Partly, this may be due to our limited understanding of the establishment and composition of the ocular microbiome. However, understanding of the establishment and composition of the ocular microbiome, may provide indicators species for early detection of IBK and to identify a window of opportunity to treat IBK before outbreaks occur. As an attempt to characterize the establishment and colonization patterns of the ocular microbiome in beef calves, we conducted a longitudinal study utilizing 239 calves. The calves were placed on three different preventative treatments which included an initial vaccination followed by a booster 3 weeks later (Autogenous, Commercial, and Placebo). Ocular swabs were collected at four different time points during summer and fall months. The V4 region of the 16S rDNA gene was sequenced from the 889 samples collected using the Illumina Miseq™ platform. The resulting sequences were analyzed using the Dada2 pipeline. The analysis demonstrated a significant difference in community composition (p< 0.001) across time periods sampled, where the microbiome reverted back to the original composition within three months of ocular microbiome perturbation and vaccination, demonstrating the resilience of the ocular microbiome to perturbation. This suggests the ocular microbiome is stable at 30 days of age. We also identified Mycoplasma sp. and Moraxella sp. which are candidate organisms known to predispose animals to IBK. Moraxella was prevalent during initial sampling, while Mycoplasma demonstrated greater abundance at all time points. This study demonstrates the diversity and the resilience of the ocular microbiome in calves and the potential to develop probiotic interventions to reduce IBK outbreaks.